Some new insights into real convergence in MENA countries’ regional areas: a spatial econometric analysis - Péridy, Nicolas; Hazem, Mohamed; Brunetto, Marc (Economics and Business Letters, 2013)
This paper proposes an analysis of real income convergence in MENA countries for more than 800 disaggregated regional areas. A spatial analysis is implemented in order to take into account the spatial interactions of GDP per capita in these areas. Moreover, a b-convergence equation (absolute and conditional) is estimated with spatially correlated errors and spatial lag models. The conditional model also includes original climate variables (temperature and precipitations) at the same geographical level. Results show that the hypothesis of regional convergence is generally accepted in most MENA countries, with the exception of Egypt and Morocco. However, the convergence process is slow and climate change in MENA countries is likely to further slowdown this process.